2017
DOI: 10.1080/14767058.2016.1237497
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of maternal neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) with birth weight

Abstract: This prospective study is the first in the literature which investigates the correlation of NLR and PLR with the week of birth and birth weight of the infant. Our study suggested that the maternal NLR and PLR are negatively correlated with the week of birth and birth weight of the infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 24 publications
5
31
3
1
Order By: Relevance
“…However, there are few studies showing the effect of hematological parameters and obtained values. Increased WBC values are also associated with poor obstetric outcomes and low birth weight [6,30]. Similarly, in the present study, WBC values were found to be higher in the group with FGR.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…However, there are few studies showing the effect of hematological parameters and obtained values. Increased WBC values are also associated with poor obstetric outcomes and low birth weight [6,30]. Similarly, in the present study, WBC values were found to be higher in the group with FGR.…”
Section: Discussionsupporting
confidence: 84%
“…A power analysis was conducted using the G * Power version 3.1.7 software and based on findings of comparable studies [6,17]. An effect size of 0.462 was used with power set at 0.80 and alpha at 0.05 to determine that a sample size of n = 59 was required in each group to conduct Student's t-test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 Previous studies have also shown that maternal inflammation affects birth weight either directly or via preterm labour. [49][50][51] In light of these findings, an increased NLR and PLR can be a result of preterm labour or insufficiency of the maternal-placental-foetal unit. A study that investigated the NLR and PLR in preeclamptic patients found a correlation between the PLR, but not the NLR, and the severity of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inflammation has been implicated in the etiology of early membrane rupture cases (3) . In the literature, the results studies evaluating the effect of PLR on neonatal outcomes vary (4,5) . The variable results can be attributed to maternal obstetric conditions (such as preterm labor, pre-eclampsia) and the different source of the blood sample (maternal/ fetal).…”
Section: To the Editormentioning
confidence: 99%